2018
DOI: 10.1099/jmmcr.0.005144
|View full text |Cite
|
Sign up to set email alerts
|

Fungemia caused by Aureobasidium pullulans in a patient with advanced AIDS: a case report and review of the medical literature

Abstract: Introduction. Aureobasidium pullulans is a dematiaceous, yeast-like fungus that is ubiquitous in nature and can colonize human hair and skin. It has been implicated clinically as causing skin and soft tissue infections, meningitis, splenic abscesses and peritonitis. We present, to our knowledge, the second case of isolation of this organism in a patient with AIDS along with a review of the literature on human infection with A. pullulans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Little is known about the predisposing factors for Aureobasidium infections. Previous case reports and studies revealed the risk factors of Aureobasidium infection, such as immunosuppressant use, steroids and HIV infection [ 21 ], cancer (with chemotherapy) [ 22 ], transplantation [ 23 ], trauma history [ 24 ], asplenia [ 25 ], leukemia [ 25 , 26 ], and parenteral nutrition [ 21 , 22 ]. Aureobasidium might be a more important pathogen in the future because of iatrogenic immunosuppression, such as solid organ transplant and massive chemotherapy, and artificial devices, such as central venous ports, would be increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the predisposing factors for Aureobasidium infections. Previous case reports and studies revealed the risk factors of Aureobasidium infection, such as immunosuppressant use, steroids and HIV infection [ 21 ], cancer (with chemotherapy) [ 22 ], transplantation [ 23 ], trauma history [ 24 ], asplenia [ 25 ], leukemia [ 25 , 26 ], and parenteral nutrition [ 21 , 22 ]. Aureobasidium might be a more important pathogen in the future because of iatrogenic immunosuppression, such as solid organ transplant and massive chemotherapy, and artificial devices, such as central venous ports, would be increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Other antifungal regimens had been reported to be effective such as amphotericin B combination with fluconazole [12,14,15], voriconazole [13], micafungin [16] or natamycin and fluconazole [10], as well as voriconazole alone [17], fluconazole alone [11] or in combination with flucytosine [1]. Unfortunately, 3 and 1 cases were unsuccessfully treated with amphotericin B [2,8,9] and with micafungin [18] resulting patient's dead subsequently. Due to lack of a standard treatment of A. pullulans peritonitis and its rarity, liposomal amphotericin B administration for 2 weeks with early catheter removal provided a good clinical outcome as presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Morais OOD reported a case of a patient with infection of the lymphatic system by A. pullulans [20]. The latest report on A. plullans infection is a case of co-infection of AIDS patients in 2018 [21]. It is generally believed that systemic infection is associated with immunodeficiency or the use of immunosuppressive agents [22].…”
Section: Discussionmentioning
confidence: 99%